CE-SDT: A new blockchain-based distributed community energy trading mechanism - Wang, Bozhi; Xu, Jinfei; Ke, Jin; Chen, C. L. Philip; Wang, Junyu; Wang, Nanxin; Li, Xi; Zhang, Fangfei; Li, Lulu (Frontiers in Energy Research, 2023)
With the spread of distributed renewable energy, residents are shifting from being mere consumers to being energy producers and consumers. This role shift poses challenges to the electricity trading mechanism that connects distributed renewable energy sources to the grid. In this paper, a new efficient and secure blockchain-based distributed community energy trading mechanism is proposed, called CE-SDT. Our system is proved to be stable and scalable. It can also help shift loads and power peaks and reduce customer costs by 60%. As a result, our proposed blockchain-based trading mechanism, as compared to the centralized trading mechanism, is applied to microgrids formed by distributed renewable energy sources, not only obtaining greater economic benefits but also reducing the carbon footprint of residents, and furthermore, it promotes low or zero-carbon configurations of the power system, thereby achieving certain environmental benefits.